Community Service On Factors Influencing Gender Roles In Agriculture In The Sinar Tani Farmers Group, Bhera Village, Mego District, Sikka Regency (International Forum of Researchers and Lecturers, 2025)
Community service activities (PKM) Gender and agricultural development in the Sinar Tani farmer group in Bhera Village, Mego District, Sikka Regency is one of the course programs in the agribusiness study program, especially the extension interest. The purpose of this activity is to overcome gender disparities in the agricultural chain and increase agricultural yields and income in the Sinar Tani farmer group. In this activity, the method used is to conduct socialization to the Sinar Tani farmer group, with the theme of factors that influence gender in agriculture. The results of this socialization program can be seen the factors that influence the role of gender in agriculture. so that women and men can know so that there is no social gap in the farmer group. Therefore, it can be concluded that the community service program from Agribusiness students of Nusa Nipa University has a positive impact in fighting for gender resilience and equality in agricultural development in Bhera village. Through active collaboration between students and the Sinar Tani farmer group, this community service program not only provides the benefits of knowledge about the factors that influence the role of gender in agriculture but also to minimize gender inequality between men and women.